Supplier Relationship Management on Sustainability: A Case Study of Education Service Commission of Uganda - Lautha Natoolo (Uganda Christian University, 2023)
The study was set to examine supplier relationship management on sustainability at the Education Service Commission of Uganda guided by three objectives namely; to examine how contract management on the economic aspect of sustainability at Education Service Commission of Uganda, to find out the influence of performance management on the social aspect of sustainability in the Education service commission of Uganda and to assess the impact of risk management on the working environment in the Education Service Commission of Uganda. The study adopted a cross-sectional survey design involves collecting data from a diverse group of participants at a single point in time. Data was collected using questionnaires which were presented to a sample of 80 respondents but only 75 questionnaires were answered and the 5 went missing. The data collected was analyzed using frequency table following the Likert scales which showed the level of agreement on respondents to the different statement. Contract management impacted the economic aspect of sustainability like leads to improved financial accountability and transparency, reducing the risk of misallocation of funds and corruption, it has led to cost savings through optimized procurement processes and better negotiation of vendor agreements and it has facilitated investments in ecofriendly technologies and practices, reducing the environmental impact of operations. Performance management has a positive influence on the social aspect of sustainability in organizations especially in terms of fostering a culture of accountability and responsibility within organizations, enhances employee well-being and engagement and aids in tracking and improving diversity and inclusion efforts, fostering a more socially responsible workplace among others. Risk management has a great impact on the working environment as it enhances employee confidence and morale, as they feel secure knowing their organization is proactive in minimizing workplace risks, improved risk management reduces the likelihood of accidents and injuries, resulting in fewer disruptions to workflow and decreased downtime, well-executed risk management practices can lead to cost savings by reducing insurance premiums and liability claims.
This is a dissertation.